PEMETAAN TINGKAT KETAHANAN PANGAN HEWANI DI INDONESIA MENGGUNAKAN METODE MULTIDIMENSIONAL SCALING - Syifa Fauziah; Fitria Virgantari; Sri Setyaningsih (EKOLOGIA, 2017)
This study aims to map the level of animal food security in Indonesia using multidimensional scaling method. The data used are secondary data obtained from the Central Bureau of Statistics, namely the average data of consumption of animal protein (gram / capita / days) and the average data of consumption of animal protein (rupiah / capita / month) in 2015 from all provinces in Indonesia. The result of the research shows that group I is food resistant in all animal food commodities, namely West Sumatra, Riau, South Sumatera, Bangka Belitung Islands, Riau Islands, Banten, West Kalimantan, Central Kalimantan, South Kalimantan, East Kalimantan and North Kalimantan. Group II is food resistant in fish, eggs and milk, less food in the meat of North Sumatra, Bengkulu, West Nusa Tenggara, North Sulawesi, West Papua and Papua. Group III is food-resistant in meat, eggs and milk, lack of food in fish such as DKI Jakarta, West Java, DI Yogyakarta, and Bali. Group IV is food-resistant in eggs and milk, less food in fish and meat such as Lampung, Central Java, and East Java. Group V is food-resistant in eggs and milk, food-susceptible to fish, and less food for less meat, namely Aceh, Central Sulawesi, South Sulawesi, Southeast Sulawesi, Gorontalo and Maluku. Group VI status is susceptible to food in fish, less food in meat, eggs and milk of West Sulawesi and North Maluku. Group VII is under-food in all animal food commodities, namely East Nusa Tenggara. Stress value of 11.15% and R2 value of 95.01% indicate that multidimensional scaling method is suitable for use in this research.Keywords: animal protein, food security, multidimensional scaling method,